Moral Values in Lasaeo Folktale for the Character Building of Young Learners - Desrin Lebagi; Magvirah Octasary; Siti Kiftiah (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study investigates the moral values of the Lasaeo folktale, a traditional folktale from Central Sulawesi, Indonesia, for character building in young learners. Employing a qualitative, descriptive approach, the research analyzes the narrative to identify embedded moral values. The researcher served as the primary instrument. The data were gathered through document analysis. The researcher then analyzed using the interactive model proposed by Miles and Huberman. The analysis revealed five core moral values within the Lasaeo folktale: obedience, responsibility, consequences of anger, importance of respect, and maintaining peace. The study comes to the conclusion that the Lasaeo folktale, which is rooted in culture, is a useful tool for promoting moral understanding, character growth, and a sense of social responsibility in early childhood education.